2017
DOI: 10.1016/j.jpain.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Long-Term Opioid Use Among Opioid Naive Patients: An Examination of Initial Prescription Characteristics and Pain Etiologies

Abstract: The relationships of characteristics of the initial opioid prescription and pain etiology with the probability of opioid discontinuation were explored in this retrospective cohort study using health insurance claims data from a nationally representative database of commercially insured patients in the U.S. We identified 1,353,902 persons aged ≥14 with no history of cancer or substance abuse, with new opioid use episodes and categorized them into 11 mutually exclusive pain etiologies. Cox Proportional Hazards m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
193
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(210 citation statements)
references
References 29 publications
12
193
3
2
Order By: Relevance
“…Prior work has shown an association between opioid prescribing practices and risk of long‐term opioid use among opioid‐naive individuals and opioid use disorder , as well as opioid overdose . Consistent with this work, this study found that long‐term opioid use (3+ months) is associated with more than double the risk of incident OUD and opioid‐related death, while the strength of the initial prescription had only a modest association.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Prior work has shown an association between opioid prescribing practices and risk of long‐term opioid use among opioid‐naive individuals and opioid use disorder , as well as opioid overdose . Consistent with this work, this study found that long‐term opioid use (3+ months) is associated with more than double the risk of incident OUD and opioid‐related death, while the strength of the initial prescription had only a modest association.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, it is essential that alongside any efforts to reduce opioid prescribing should be simultaneous efforts to improve treatment of pain and minimize disparities in access to effective analgesia [46,47]. Prior work has shown an association between opioid prescribing practices and risk of long-term opioid use among opioid-naive individuals [32,48,49] and opioid use disorder [50], as well as opioid overdose [35]. Consistent with this work, this study found that long-term opioid use (3+ months) is associated with more than double the risk of incident OUD and opioid-related death, while the strength of the initial prescription had only a modest association.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of the current opioid epidemic, as increasing evidence emerges on the dangers of overprescribing opioids, surgical oncologists must be prepared to alter their practice on the basis of the evidence. Until recently, patients with oncology were often excluded from opioid studies that focused on acute pain . Given the excellent long‐term survival from breast cancer, such patients are at risk of chronic opioid abuse that is not necessarily related to cancer pain .…”
Section: Discussionmentioning
confidence: 99%
“…However, we documented meaningful variation by region and resident characteristics, which may indicate that improvements are possible. Further, the proportion initiating long‐acting opioids was higher than reports from community‐dwelling populations and raises additional questions on how long‐acting opioids are initiated in frail elderly nursing home residents …”
Section: Discussionmentioning
confidence: 87%
“…Nursing home residents appeared to have a higher proportion of initiators prescribed long‐acting opioids than community‐dwelling populations in the United States including veterans with chronic pain (1.9% between 2000 and 2009), commercially insured persons (0.5% in 2 studies between 2006 and 2015), older adults with Medicare Advantage (0.9% between 2009 and 2015), and disabled adults with Medicare (1.9% between 2009 and 2015) . Given that the proportion of initiators prescribed long‐acting opioids is higher among older adults and other populations with a higher burden of painful comorbidities, it is possible that the risk of naively initiating long‐acting opioids is higher in those with more severe pain.…”
Section: Discussionmentioning
confidence: 99%